2020
DOI: 10.1302/2046-3758.16.bjo-2020-0062.r1
|View full text |Cite
|
Sign up to set email alerts
|

Trauma surgery at a designated COVID-19-free site during the pandemic

Abstract: Aims Elective operating was halted during the COVID-19 pandemic to increase the capacity to provide care to an unprecedented volume of critically unwell patients. During the pandemic, the orthopaedic department at the Aneurin Bevan University Health Board restructured the trauma service, relocating semi-urgent ambulatory trauma operating to the isolated clean elective centre (St. Woolos’ Hospital) from the main hospital receiving COVID-19 patients (Royal Gwent Hospital). This study presents our experience of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…At the time of the study, routine COVID-19 testing was not available and instead patients were screened for symptoms of COVID-19 at presentation and again on admission. All patients included were asymptomatic at the time of follow-up telephone consultation which is largely in keeping with our own results and supports our suggestion that our protocol is a safe approach to providing elective orthopaedic services [ 14 ]. That said, Lei et al .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…At the time of the study, routine COVID-19 testing was not available and instead patients were screened for symptoms of COVID-19 at presentation and again on admission. All patients included were asymptomatic at the time of follow-up telephone consultation which is largely in keeping with our own results and supports our suggestion that our protocol is a safe approach to providing elective orthopaedic services [ 14 ]. That said, Lei et al .…”
Section: Discussionsupporting
confidence: 84%
“…However, a limitation is that our patients did not undergo routine post-operative COVID-19 testing. That said, this approach has also had no negative implications in other studies which used targeted COVID-19 testing for symptomatic staff members only [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lazizi et al 26 and Clough et al 27 have both demonstrated low rates of postoperative COVID-19 after hip and general trauma surgery on “cold” and elective sites of 4% and 0.9%, respectively. Gonzi et al 28 also demonstrated a zero rate of postoperative COVID-19 in a cohort of 58 patients undergoing orthopaedic surgery, the majority being related to trauma, at a COVID-19 free site. Zahra et al 3 described their “green” COVID-19 free elective orthopaedic pathway which demonstrated a high rate of patient satisfaction and a low rate of postoperative COVID-19, with only one of their 100 patients developing asymptomatic SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 92%
“…10 However, there are little data available about change in patient preferences and how private ("COviD-light") hospitals may influence these decisions. 11,12 in the UK, patients have been identified by nHs england and their general practitioners as either 'moderate risk' or 'high risk' based on their age and medical history. 13 patients classified as 'high risk' were advised to limit faceto-face contact as much as possible.…”
Section: Introductionmentioning
confidence: 99%